(untitled) (Contemporary Mathematics, 2023)
An increase in municipal waste has become one of the biggest problems today. Managing waste is a big challenge for every country. Municipal waste management includes transportation and recycling of waste, which needs huge funds. Moreover, significant carbon emissions occur while transporting garbage from one site to another. Thus, this study focuses on reducing the cost due to municipal solid waste (MSW) transportation. The research aims to develop a mathematical model of the supply chain of MSW management. The process of segregation and recycling is also considered in this study. We consider six Indian states and identify the dumping location of the garbage. The study proposes an efficient framework for selecting the segregation hub location and location of MSW treatment plants. The outcomes would be beneficial to achieve an efficient waste management strategy with reduced cost. The numerical simulation results of the model provides the minimum transportation cost as Rs. 4.92 × 106 according to the locations selected for the study. The final strategic decisions is feasible under the constraint sets considered in the model.